Space and Order in Antebellum American Temperance - Nyberg, Ferdinand (Tübingen University Press, 2024)
This book explores the role of social space in American temperance discourse of the antebellum era. It specifically charts how, through engagements with space, temperance advocates located and expressed the existence of an ‘alcoholic order.’ Variously referred to as ‘King Alcohol’ or the ‘Rum System,’ this alcoholic order was portrayed as ubiquitous and threatening. Recording the machinations and ubiquity of this order would help temperance claims surrounding the threat of alcohol appear meaningful and true. Discursively engaging with social spaces, advocates could convey a world that was dominated and ordered by alcohol’s production and consumption. Each empirical chapter of this book explores a discrete space – the latter ranging in downward scale – and shows how, through these spaces, advocates went about identifying the lineages and historical linkages of alcoholic damage. First, advocates portrayed the American public sphere as being borne on and tainted by alcoholic connections; through such engagements with the public, the American present was condemned as a centrally alcoholic arrangement. Second, advocates frequently portrayed the Atlantic world as an alcoholic space, thus infusing temperance with critiques of global capitalism and slavery. Third, a focus on the United States as a country and its booze-soaked history helped advocates’ espousals of a temperance-led future for the country. Finally, the drunkard’s body served to support key temperance claims – especially surrounding health and hygiene – while also suffusing activism with critiques of a reigning false consciousness. Throughout the book, temperance advocates’ efforts of archiving the damages of drink – that is, of recording alcohol’s history and harm – are traced. In so doing, advocates could expound the existence of an alcoholic order, adversely impacting the world. By focussing on a discrete space, each chapter reveals novel angles of temperance; far from being merely an assault on drink, we come to appreciate temperance as a wide-ranging imaginary. Each space is connected to the other, in the writings of temperance advocates, through the reigning alcoholic order. Yet each space also brings up its own set of societal issues. In writing about the public, temperance comes to be a negotiation of issues surrounding individuality, gender, work, and capitalism. The Atlantic, on the other hand, carries forth such issues of capitalism and the market and has temperance advocates interrogate questions surrounding freedom, slavery, agency, and race. Similar questions surrounding freedom find echoes in advocates’ writings surrounding the country: temperance here comes to revolve around ideology, nationalism, and individualism. Lastly, writings surrounding the body brings forth issues of surrounding the individual and individualism, by focussing especially on workers’ alienation, on masculinity, and race.